USP38 exacerbates pressure overload-induced left ventricular electrical remodeling - Yucheng Pan; Zheng Xiao; Hongjie Yang; Bin Kong; Hong Meng; Wei Shuai; He Huang (BMC, 2024)
Abstract Background Ubiquitin-specific protease 38 (USP38), belonging to the USP family, is recognized for its role in controlling protein degradation and diverse biological processes. Ventricular arrhythmias (VAs) following heart failure (HF) are closely linked to ventricular electrical remodeling, yet the specific mechanisms underlying VAs in HF remain inadequately explored. In this study, we examined the impact of USP38 on VAs in pressure overload-induced HF. Methods Cardiac-specific USP38 knockout mice, cardiac-specific USP38 transgenic mice and their matched control littermates developed HF induced by aortic banding (AB) surgery. After subjecting the mice to AB surgery for a duration of four weeks, comprehensive investigations were conducted, including pathological analysis and electrophysiological assessments, along with molecular analyses. Results We observed increased USP38 expression in the left ventricle of mice with HF. Electrocardiogram showed that the USP38 knockout shortened the QRS interval and QTc, while USP38 overexpression prolonged these parameters. USP38 knockout decreased the susceptibility of VAs by shortening action potential duration (APD) and prolonging effective refractory period (ERP). In addition, USP38 knockout increased ion channel and Cx43 expression in ventricle. On the contrary, the increased susceptibility of VAs and the decreased expression of ventricular ion channels and Cx43 were observed with USP38 overexpression. In both in vivo and in vitro experiments, USP38 knockout inhibited TBK1/AKT/CAMKII signaling, whereas USP38 overexpression activated this pathway. Conclusion Our data indicates that USP38 increases susceptibility to VAs after HF through TBK1/AKT/CAMKII signaling pathway, Consequently, USP38 may emerge as a promising therapeutic target for managing VAs following HF.